Arabidopsis thaliana WRKY25 Transcription Factor Mediates Oxidative Stress Tolerance and Regulates Senescence in a Redox-Dependent Manner - Doll, Jasmin; Muth, Maren; Riester, Lena; Nebel, Sabrina; Bresson, Justine; Lee, Hsin-Chieh; Zentgraf, Ulrike (Frontiers in Plant Science, 2020)
Senescence is the last developmental step in plant life and is accompanied by a massive change in gene expression implying a strong participation of transcriptional regulators. In the past decade, the WRKY53 transcription factor was disclosed to be a central node of a complex regulatory network of leaf senescence and to underlie a tight multi-layer control of expression, activity and protein stability. Here, we identify WRKY25 as a redox-sensitive up-stream regulatory factor of WRKY53 expression. Under non-oxidizing conditions, WRKY25 binds to a specific W-box in the WRKY53 promoter and acts as a positive regulator of WRKY53 expression in a transient expression system using Arabidopsis protoplasts, whereas oxidizing conditions dampened the action of WRKY25. However, overexpression of WRKY25 did not accelerate senescence but increased lifespan of Arabidopsis plants, whereas the knock-out of the gene resulted in the opposite phenotype, indicating a more complex regulatory function of WRKY25 within the WRKY subnetwork of senescence regulation. In addition, overexpression of WRKY25 mediated higher tolerance to oxidative stress and the intracellular H2O2 level is lower in WRKY25 overexpressing plants and higher in wrky25 mutants compared to wildtype plants suggesting that WRKY25 is also involved in controlling intracellular redox conditions. Consistently, WRKY25 overexpressers had higher and wrky mutants lower H2O2 scavenging capacity. Like already shown for WRKY53, MEKK1 positively influenced the activation potential of WRKY25 on the WRKY53 promoter. Taken together, WRKY53, WRKY25, MEKK1 and H2O2 interplay with each other in a complex network. As H2O2 signaling molecule participates in many stress responses, WRKK25 acts most likely as integrators of environmental signals into senescence regulation.